Small & chic interiors : how to make the most of mini spaces - Gutierrez, Manel Couto; Velilla, Aleix Ortuno (Singapore : Page One, 2014)
It would be impossible to look at these and not want your own. In an increasingly crowded world, where homes must squeeze the most out of available space, the challenge lies in the search for creative solutions to meet new space requirements. The use of new technologies and strategies are essential to optimize every square foot. This book is profusely illustrated with beautiful examples offering the reader inspiring and creative ideas developed by today's most forward-thinking interior designers.
Parallel text in English, German, French, Spanish.
Keywords: Small rooms; Interior architecture; Interior decoration